Anatomical and clinical relevance of Kager’s triangle: diagnostic approaches and therapeutic implications for related pathologies - Eren Ogut (Journal of Orthopaedic Surgery and Research)
Abstract Background Kager’s triangle (KT) is an anatomically defined space in the posterior ankle, bordered by the Achilles tendon (AT), flexor hallucis longus (FHL), and superior margin of the calcaneus. It contains Kager’s fat pad (KFP), which plays a crucial role in ankle biomechanics and is implicated in several pathologies, including Achilles tendinopathy, retrocalcaneal bursitis, and posterior ankle impingement syndrome (PAIS). This review aimed to evaluate the anatomical, radiological, and clinical characteristics of the KT and assess its diagnostic and therapeutic relevance in posterior ankle disorders. Methods A comprehensive literature search was conducted in PubMed, Web of Science, and Google Scholar in December 2024. The inclusion criteria encompassed studies addressing the anatomy, pathology, and imaging of the KT and its adjacent structures. Data on KT dimensions, imaging findings, clinical presentations, and treatment outcomes were collected. Results KT was significantly associated with age, sex, AT length, and KFP atrophy. MRI signal changes within the KT correlated with the severity of Achilles tendinopathy (p < 0.01). KT effacement and edema were predictive of retrocalcaneal bursitis. Dynamic interactions between the KT and surrounding tendinous structures influence local stress distribution and may trigger inflammation or degeneration. Conclusions KT serves as both a biomechanical buffer and diagnostic marker for several posterior ankle pathologies. Morphometric assessment via radiography or MRI can support early diagnosis and guide personalized treatment planning. Additional prospective studies employing standardized protocols are necessary to ascertain its clinical utility.